Análise comparativa do uso das técnicas de nucleação para recuperação de áreas degradadas - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
The recovery of areas degraded by human activity requires the use of different techniques involving multidisciplinary knowledge, being mandatory not only due to environmental legislation, but due to the pressure currently exerted by public opinion on companies and governments. Every mining project, or any other activity that causes environmental impacts, before the implementation process, must present studies of the impacts caused by the installation and what mitigation measures will be taken. In this context, there is the recovery of the areas used during the execution of the project, that is, how the impacted area will be rehabilitated so that it can be used for another purpose, or being recovered as it once was, before the process that modified it. Several techniques are used with the aim of recovering areas that have undergone anthropic processes, either through the traditional method of planting seedlings, or through the insertion of recovery nuclei, called nucleating techniques or nucleation. The present work aims to make a comparative analysis from experiences with the use of nucleation techniques to recover areas degraded by human activity, in order to demonstrate the positive efficiency in the use of nucleation in these processes.
Keywords: Nucleação; Áreas degradadas; Recuperação; CNPQ:: CIÊNCIAS EXATAS